The Role of Agricultural Extension in Increasing Competence and Income Rice Farmers - Managanta, Andri Amaliel (Talenta Publisher, 2020)
The success of agricultural development in Indonesia in developing the ability of farmers is inseparable from the role of extension services carried out professionally. This study aims to (1) Analyzing the level of farmers 'perceptions about the role of extension workers in improving the competence of rice farmers in Tayawa Village, and (2) Analyzing factors that influence the level of farmers' perceptions about the role of extension workers in increasing the competence of rice farmers in Tayawa Village. This research uses a survey method with a descriptive analysis approach and a quantitative paradigm, supplemented with qualitative data information to support and sharpen quantitative analysis. The level of competence of middle rice farmers tends to be low, due to the weak role of agricultural extension workers. The role of the instructor as a communicator, facilitator, educator, and communicator turned out to have a positive effect on increasing the competence of rice farmers. But now these factors tend to be low so that it is still lacking in efforts to increase the competence of rice farmers.